URGENSI PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENANGANI DEGRADASI TATA KRAMA PADA ANAK USIA SEKOLAH DASAR - Yohamintin, Yohamintin; Mutsaqofah, Marsa Bila; Nafasabilla, Zaskia; Syaqina, Dianita Widya; Fadhilah, Hasna Khalishah (Universitas Muhammadiyah Tangerang, 2024)
Indonesia is one of the countries known for its culture of manners. However, at this time there is rampant degradation of manners, especially in elementary school-age children. Therefore, this research aims to find out the urgency of strengthening the Pancasila student profile in dealing with the degradation of manners in elementary school-age children. This research uses a qualitative method with a type of literature study that aims to describe the findings of researchers on several scientific journal articles found according to the topic of discussion so that the results of the discussion are obtained. The conclusion of this research is that understanding and awareness of Pancasila values is very important for elementary school children because Pancasila values are not only a moral and ethical guide, but also a reference in shaping the character of a quality young generation. The factors causing the degradation of manners of elementary school-age children are family factors, environment and socialization, and gadget/internet/social media factors. In addition, the positive impact resulting from strengthening the profile of Pancasila students is quite good in shaping children's character, can increase students' moral awareness. Therefore, the urgency of strengthening the Pancasila learner profile is very important in the context of shaping children's manners.